2001
DOI: 10.1002/jemt.1180
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in insect olfaction, specifically regarding the morphology and sensory physiology of antennal sensilla of the female sphinx moth Manduca sexta

Abstract: The antennal flagellum of female Manduca sexta bears eight sensillum types: two trichoid, two basiconic, one auriculate, two coeloconic, and one styliform complex sensilla. The first type of trichoid sensillum averages 34 μm in length and is innervated by two sensory cells. The second type averages 26 μm in length and is innervated by either one or three sensory cells. The first type of basiconic sensillum averages 22 μm in length, while the second type averages 15 μm in length. Both types are innervated by th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
52
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(58 citation statements)
references
References 132 publications
(171 reference statements)
3
52
0
Order By: Relevance
“…Both inhibitory and excitatory responses have been reported in insect primary olfactory neurons (de Bruyne et al, 2001;Shields and Hildebrand, 2001;Hallem et al, 2004;Tichy et al, 2005;Yao et al, 2005) and their odorant receptors . The frequency response approach allowed us to detect simultaneous excitation and inhibition in multiple neurons within a sensillum during the same stimulation by fluctuating concentrations of odorants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both inhibitory and excitatory responses have been reported in insect primary olfactory neurons (de Bruyne et al, 2001;Shields and Hildebrand, 2001;Hallem et al, 2004;Tichy et al, 2005;Yao et al, 2005) and their odorant receptors . The frequency response approach allowed us to detect simultaneous excitation and inhibition in multiple neurons within a sensillum during the same stimulation by fluctuating concentrations of odorants.…”
Section: Discussionmentioning
confidence: 99%
“…Inhibitory responses in insect olfaction include cockroach antennal sensilla responding with opposite polarity to lemon oil (Tichy et al, 2005), Manduca sexta olfactory sensilla giving inhibitory responses to a range of odorants (Shields and Hildebrand, 2001), Drosophila basiconic and coeloconic sensilla inhibited by some food odorants and terpenes (de Bruyne et al, 2001;Yao et al, 2005), and Drosophila trichoid sensilla inhibited by fruit odorants (Hallem et al, 2004). A survey of some Drosophila olfactory receptor molecules to a wide range of odorants found 17% excitatory versus 11% inhibitory responses .…”
Section: Introductionmentioning
confidence: 99%
“…Many recent studies, however, have clarified that broad or general tuning, as indicated by previous studies, is a result of two common experimental practices: the lack of screens identifying the actual key ligands for these ORNs; and the concentrations at which kairomones were applied were many hundreds of times higher than environmentally and physiologically relevant (e.g. , Dickens 1990, Heinbockel and Kaissling 1996, Larsson et al 2001, Priesner 1979, Shields and Hildebrand 2001, Skiri et al 2004. Kazama and Wilson (2008), working with D. melanogaster, have determined that high volatile concentrations, which result in high ORN spike frequencies, dampen AL input receptivity and thus, high frequency ORN responses are not the optimal characteristics by which to identify key ligands.…”
Section: Selectivitymentioning
confidence: 99%
“…sexta is a moth that belongs to the order Lepidoptera; defoliators of tobacco, tomato, and other plants of the Solanaceae family characterize this group of insects and are present over much of the American continent. Because of its large size, M. sexta has served as a model organism to study the mechanism of action of Cry toxins from Bt (Shields and Hildebrand 2001;Kanost et al 2004;Pigott and Ellar 2007). Even for this important model organism, there was very little genetic information available before 2008, when Zou et al through a transcriptome analysis using the first generation of pyrosequencing technology of 454 identified a large number of ESTs associated with hemolymph and immune system which considerably increased the genomic information available for this organism (Zou et al 2008).…”
Section: Transcriptome As Tool To Identify New Proteins Involved In Tmentioning
confidence: 97%